2018
DOI: 10.11606/1807-5509201800020189
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ceramic-impregnated clothing on a 10 km running performance

Abstract: This study aimed to analyze the effects of using bioceramic clothing on the 10 km running performance. Ten healthy young males (age 27.9 ± 4.2 years; height 1.8 ± 0.1 m; body mass 73.0 ± 7.5 kg; body mass index (BMI) 23.5 ± 2.3 kg·m2 and body fat 19.3 ± 4.2 %) volunteered to participate in the study. The participants visited the track for three 10 km performances under different conditions: bioceramic clothes (CER), placebo (PLA) and personal clothes (C). Test order was randomized and subjects were blind to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…A total of eleven studies were ultimately identified and included in this review (Table 1). Thereafter, selected studies were classified into two different categories according to their experimental design: six studies investigated the 'effects of FIR-emitting garments worn during exercise' [16,[30][31][32][33][34], and five studies investigated the 'effects of FIR-emitting garments worn post-exercise' [35][36][37][38][39].…”
Section: Plos Onementioning
confidence: 99%
See 4 more Smart Citations
“…A total of eleven studies were ultimately identified and included in this review (Table 1). Thereafter, selected studies were classified into two different categories according to their experimental design: six studies investigated the 'effects of FIR-emitting garments worn during exercise' [16,[30][31][32][33][34], and five studies investigated the 'effects of FIR-emitting garments worn post-exercise' [35][36][37][38][39].…”
Section: Plos Onementioning
confidence: 99%
“…Participants' age ranged from 18 to 57 years. All the studies had samples sizes of five to twenty participants, with only males [30,31,34] or a mixture of female and male participants [16,32,33]. In the studies testing FIR-emitting garments post-exercise, participants were recreationally active [36][37][38] or elite male athletes [35,39], and their age ranged from 19 to 26 years except in one study where the participants were > 60 years old [37].…”
Section: Samplesmentioning
confidence: 99%
See 3 more Smart Citations